Endosymbiosis allows Sitophilus oryzae to persist in dry conditions - Kanyile, Sthandiwe Nomthandazo; Engl, Tobias; Heddi, Abdelaziz; Kaltenpoth, Martin (Frontiers in Microbiology, 2023)
Insects frequently associate with intracellular microbial symbionts (endosymbionts) that enhance their ability to cope with challenging environmental conditions. Endosymbioses with cuticleenhancing microbes have been reported in several beetle families. However, the ecological relevance of these associations has seldom been demonstrated, particularly in the context of dry environments where high cuticle quality can reduce water loss. Thus, we investigated how cuticle-enhancing symbionts of the rice-weevil, Sitophilus oryzae contribute to desiccation resistance. We exposed symbiotic and symbiont-free (aposymbiotic) beetles to long-term stressful (47% RH) or relaxed (60% RH) humidity conditions and measured population growth. We found that symbiont presence benefits host fitness especially under dry conditions, enabling symbiotic beetles to increase their population size by over 33-fold within three months, while aposymbiotic beetles fail to increase in numbers beyond the starting population in the same conditions. To understand the mechanisms underlying this drastic effect, we compared beetle size and body water content and found that endosymbionts confer bigger body size and higher body water content. While chemical analyses revealed no significant differences in composition and quantity of cuticular hydrocarbons after long-term exposure to desiccation stress, symbiotic beetles lost water at a proportionally slower rate than did their aposymbiotic counterparts. We posit that the desiccation resistance and higher fitness observed in symbiotic beetles under dry conditions is due to their symbiont-enhanced thicker cuticle, which provides protection against cuticular transpiration. Thus, we demonstrate that the cuticle enhancing symbiosis of Sitophilus oryzae confers a fitness benefit under drought stress, an ecologically relevant condition for grain pest beetles. This benefit likely extends to many other systems where symbiontmediated cuticle synthesis has been identified, including taxa spanning beetles and ants that occupy different ecological niches.